Instability in the Cee Banking System. Evidence from the Recent Financial Crisis - Renata Karkowska (CES Working Papers, 2013)
Sparked by the recent great recession and the role of financial markets, considerable interest exists among researchers within both the academic and public community in measuring and modeling systemic risk. This article introduces a new framework for measuring systemic risk by using a risk-adjusted balance sheet approach. In this regard, the analysis of 21 largest commercial banks operating in 7 countries from Central and Eastern Europe, shows potential risk which could threaten all the financial system. The paper concludes new directions for measuring systemic risk by using Merton model. It shows how risk management tools can be applied in new ways to measure and analyze systemic risk in European banking system.
Keywords: G1; G11; G10; E44; 330; systemic risk; Merton model; financial crisis; banking system Romania